Digital Strategies and Behavior Change Techniques for Preventing Sexually Transmitted Infections: Protocol for an Overview of Systematic Reviews; [Estrategias Digitales y Técnicas de Cambio de Comportamiento Para la Prevención de Infecciones de Transmisión Sexual: Protocolo Para Una Revisión de Revisiones Sistemáticas] - Duarte-Anselmi, G (Medwave Estudios Ltda, 2025)
INTRODUCTION Sexually transmitted infections (STIs) are a leading cause of premature mortality, with unsafe sex as a predominant risk factor. Changing risky sexual behaviors and adopting healthy habits is key to preventing STIs, including HIV, essential for public health. Technological advances in digital interventions have revealed significant opportunities, and systematic reviews have evaluated their effectiveness. These digital interventions, using technologies such as mobile phones, apps, and wearable devices, have shown great potential to reduce STIs, particularly among young people, who are a key population for their implementation. OBJECTIVE This protocol aims to describe in advance a systematic review intended to gather, evaluate, and synthesize the available evidence on digital behavior change interventions for STI prevention. In particular, it seeks to identify the most effective behavior change techniques to guide the design of evidence-based interventions that contribute to reducing STIs. METHODS This protocol outlines a review of systematic reviews. The methodological quality of the included reviews will be assessed using the AMSTAR-2 tool, following the PRISMA-P guidelines. Comprehensive searches will be conducted in Cochrane, PubMed, Epistemonikos, and PsycINFO. The inclusion criteria will focus on systematic reviews evaluating the effect of digital behavior change interventions for STI prevention, covering technologies such as mobile phones, apps, and websites. Data extraction will identify key components using the Behavior Change Techniques Taxonomy version 1 (BCTTv1). The protocol is registered in PROSPERO (CRD42023485887). EXPECTED RESULTS This review is expected to provide theoretical insights into behavior change in STI prevention through digital interventions, identifying the most effective techniques. These findings will help design scalable, evidence-based interventions, aimed especially at youth, and guide policymakers in implementing more effective strategies to reduce STI transmission around the world. © 2025, Medwave Estudios Ltda. All rights reserved.